2022
DOI: 10.1039/d2fo00480a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of Laminaria japonica fucoidan in high-fat diet-fed mice vary with the gut microbiota structure

Abstract: The present study amied to investigate the possible discrepancy of anti-obesity effects of fucoidan supplementation in high-fat diet-fed mice models with different gut microbiota communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, it has been reported that various polysaccharides can be fermented by specific intestinal bacteria or enhance the SCFAs-producing bacteria to promote the production of SCFAs, which contributed to its anti-obesity effect. 20 However, Zhang et al 21 reported that fucoidan obtained from L. japonica can relieve mice obesity via modulating gut microbiota structure, but this anti-obesity effect is not dependent on producing SCFAs by gut microbiota. In the present study, CLP administration also had no effect on SCFAs production, suggesting the anti-obesity effect of CLP was uncorrelated with the production of SCFAs, and the results were in line with the gut microbiota analyses for which the supplement of CLP had no effect on enriching SCFAs-producing bacteria (Figs 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that various polysaccharides can be fermented by specific intestinal bacteria or enhance the SCFAs-producing bacteria to promote the production of SCFAs, which contributed to its anti-obesity effect. 20 However, Zhang et al 21 reported that fucoidan obtained from L. japonica can relieve mice obesity via modulating gut microbiota structure, but this anti-obesity effect is not dependent on producing SCFAs by gut microbiota. In the present study, CLP administration also had no effect on SCFAs production, suggesting the anti-obesity effect of CLP was uncorrelated with the production of SCFAs, and the results were in line with the gut microbiota analyses for which the supplement of CLP had no effect on enriching SCFAs-producing bacteria (Figs 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that various polysaccharides can be fermented by specific intestinal bacteria or enhance the SCFAs‐producing bacteria to promote the production of SCFAs, which contributed to its anti‐obesity effect 20 . However, Zhang et al 21 . reported that fucoidan obtained from L. japonica can relieve mice obesity via modulating gut microbiota structure, but this anti‐obesity effect is not dependent on producing SCFAs by gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in weight was mainly attributed to reduced visceral fat mass by approximately 18%. Previously, several studies have reported that fucoidan treatment successfully reduced the chance of obesity in rats (Wang et al, 2021;Zuo et al, 2022;Zhang et al, 2022b). According to Kim et al (2014b), the animal that was given an HFD and fucoidan showed less body weight increase, a lower food-efficiency ratio and less relative liver and epididymal fat content than an HFD alone.…”
Section: Physical Changes and Anti-obesity Parametersmentioning
confidence: 99%
“…5,8 Fucoidan, a kind of sulfated polysaccharide, is mainly distributed in brown algae cell walls and has significant physiological effects such as anti-inflammation, anti-obesity, and immune regulation. 5,10,11 However, the underlying metabolic mechanism of its effects in vitro and in vivo is still unclear. It has been proved that fucoidan cannot be digested by gastrointestinal enzymes or acid liquids.…”
Section: Introductionmentioning
confidence: 99%